2005
DOI: 10.1111/j.1440-1746.2005.04051.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of gastric function after Helicobacter pylori eradication in subjects with body atrophic gastritis: Prospective 4‐year study

Abstract: After H. pylori eradication, subjects with body atrophic gastritis showed long-term improvement of physiological gastric function, reflected by significantly and continually increasing sPGI levels over a 4-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…25 Further, Di Mario et al examined PG I levels following H. pylori eradication in patients with moderate-tosevere atrophic gastritis and showed that in 23 patients with PG I levels <25 ng/mL pre-eradication, levels increased from a pre-eradication average of 11.7 to 17.4 ng/mL at 6 months post-eradication, reaching 32.7 ng/mL at 4 years. 29 In the present study, PG I levels dropped from a 61.4 ng/mL pre-eradication to 35.9 ng/mL 2 months after successful eradication, then rose to 41.5 ng/mL at 12 months and 41.9 ng/mL at 24 months. In other words, PG I level decreased following successful eradication as inflammation of the gastric mucosa was reduced and then increased with the appearance of regenerative epithelium cells in the atrophic mucosa.…”
Section: Discussionsupporting
confidence: 45%
“…25 Further, Di Mario et al examined PG I levels following H. pylori eradication in patients with moderate-tosevere atrophic gastritis and showed that in 23 patients with PG I levels <25 ng/mL pre-eradication, levels increased from a pre-eradication average of 11.7 to 17.4 ng/mL at 6 months post-eradication, reaching 32.7 ng/mL at 4 years. 29 In the present study, PG I levels dropped from a 61.4 ng/mL pre-eradication to 35.9 ng/mL 2 months after successful eradication, then rose to 41.5 ng/mL at 12 months and 41.9 ng/mL at 24 months. In other words, PG I level decreased following successful eradication as inflammation of the gastric mucosa was reduced and then increased with the appearance of regenerative epithelium cells in the atrophic mucosa.…”
Section: Discussionsupporting
confidence: 45%
“…The prevalence of corpus atrophy, as evaluated by means of sPGI levels, was 10.7% for CpAG and 3.6% for ApAG, with a global figure of 14.3%. These estimates are in line with those of other studies (24,38). It is notable that 12% of the patients affected by corpus atrophic gastritis were -30-year-old, eliciting not only clinical, but also ''social'' interest.…”
Section: Discussionsupporting
confidence: 88%
“…It is notable that 12% of the patients affected by corpus atrophic gastritis were -30-year-old, eliciting not only clinical, but also ''social'' interest. This is of practical importance in that the possibility exists that patients with atrophic gastritis can revert to normal physiological gastric functions and normal mucosa after successful eradication of H. pylori (38). In this way, particularly in young people, the well-known Correa's stepwise cascade can be interrupted, thus preventing more severe histological alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kokkola et al reported increased levels of PG I in patients with moderate‐to‐severe atrophic gastritis, from a 16.3 ng/mL pre‐eradication to 25.7 ng/mL post‐eradication 25 . Further, Di Mario et al examined PG I levels following H. pylori eradication in patients with moderate‐to‐severe atrophic gastritis and showed that in 23 patients with PG I levels <25 ng/mL pre‐eradication, levels increased from a pre‐eradication average of 11.7 to 17.4 ng/mL at 6 months post‐eradication, reaching 32.7 ng/mL at 4 years 29 . In the present study, PG I levels dropped from a 61.4 ng/mL pre‐eradication to 35.9 ng/mL 2 months after successful eradication, then rose to 41.5 ng/mL at 12 months and 41.9 ng/mL at 24 months.…”
Section: Discussionmentioning
confidence: 99%